2014
DOI: 10.1016/j.phrs.2013.11.009
|View full text |Cite
|
Sign up to set email alerts
|

Defining the blanks – Pharmacochaperoning of SLC6 transporters and ABC transporters

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
59
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(60 citation statements)
references
References 104 publications
1
59
0
Order By: Relevance
“…GlyT2 oligomerization was previously shown after transporter crosslinking (49). Our data confirm that oligomer formation is required for ER export, as demonstrated for other SLC6 transporters (26). Therefore, the immature GlyT2 forms appear to bind to CNX prior to the formation of oligomers, and they are subsequently exported from the ER to continue transporter maturation.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…GlyT2 oligomerization was previously shown after transporter crosslinking (49). Our data confirm that oligomer formation is required for ER export, as demonstrated for other SLC6 transporters (26). Therefore, the immature GlyT2 forms appear to bind to CNX prior to the formation of oligomers, and they are subsequently exported from the ER to continue transporter maturation.…”
Section: Discussionsupporting
confidence: 84%
“…TM1a is connected to internal loop 1, which in turn is hydrogen-bonded to the C-terminal latch of the transporter. In several SLC6 members, this region contains the binding site for the cargo receptor of the COPII complex Sec24 that permits ER export (26,39), and C-terminal deletion mutants of GlyT2 are retained in the ER (32). We have demonstrated that the interaction of wild-type GlyT2 with Sec24D is altered in the S512R mutant.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…However previous work has not assessed the ability of pharmacological chaperones to rescue disease-relevant mutations. Disease relevant mutations are not restricted to the C terminus but are instead found throughout the protein clustered at the protein-lipid interface (36). We, therefore, tested bupropion and ibogaine on four DTDS mutations: L224P, A314V, R445C, and P529L.…”
Section: Pharmacological Chaperones Of the Dopamine Transportermentioning
confidence: 99%
“…Last but not least, the communication between protomers may have repercussions that go beyond the actions of amphetamines. There are several variations in the coding sequence of SLC6 transporters, some of which are associated with folding defects and thus giving rise to overt clinical phenotypes (Chiba et al 2014). However, there are also single-nucleotide polymorphisms, which trigger changes in the coding sequence, which give rise to functional transporters, e.g.…”
Section: The Biological Importance Of Cooperativity Between Transportmentioning
confidence: 99%